Questions-réponses : les NTIC et la certification des forêts - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
La certification des forêts est un instrument relativement nouveau qui encourage la gestion durable des forêts.